Pengaruh Pijat Bayi Terhadap Kualitas Tidur Bayi Usia 1-3 Bulan - Nurmupida Abbas; Amelia Nur Hidayanti; Okky Merben (JURNAL KESEHATAN TERAPAN, 2026)
Good sleep quality is very important for the growth and development of babies aged 0-6 months. One factor that can affect sleep quality is baby massage. The purpose of this study is the effect of baby massage on the sleep quality of babies aged 1-3 months at TPMB Jamilah, Pesanggrahan District, South Jakarta. The study used a pre-experimental design with a one group pre-test post-test design approach. The population in this study were mothers who had babies aged 1-3 months with a sample of 35 people taken using the total sampling technique. The instruments used included the KPSP sheet and the baby massage SOP. Data analysis tests used the Shapiro Wilk test and paired samples T-test. The results of the paired samples T-test showed that there was a significant difference between the quality of baby sleep before and after baby massage (p <0.05). Conclusion: that baby massage has a significant effect on improving the quality of baby sleep.